Pengaruh Pengetahuan Pemilik, Skala Usaha, dan Umur Usaha terhadap Keberhasilan Kinerja Usaha dengan Penggunaan Informasi Akuntansi sebagai Variabel Moderasi (Survei pada Pemilik Usaha UKM Makanan Khas di Kabupaten Banyumas) - Utami, Hastin Tri (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2018)
This study aimed to determine the influence of owner’s knowledge, business scale, busines life partially toward the success of business performance and also to determine the influence of owner’s knowledge, business scale, business life partially toward the success of business performance with using of accounting information as moderating variable. The population of this study is SME’s (Small Medium Enterprises) owners of Banyumas specialty food. Sample determining is using purposive sampling method. The respondents consist of 64 business owners. Hypotheses testing of this study use multiple linear regression and Moderated Regression Analysis (MRA). Based on the research result and data analysis using multiple linear regression and MRA show that : (1) owner’s knowledge has positive significant influence to the success of business performance; (2) business scale has positive significant influence to the success of business performance; (3) business life has positive significant influence to the success of business performance; (4) using of accounting information moderated positively toward the relationship of owner knowledge to the success of business performance; (5) using of accounting information moderated positively toward the relationship of business scale to the success of business performance; (6) using of accounting information moderated positively toward the relationship of business life to the success of business performance. The limitation of this study are: (1) independent variables only focus on internal business factors such as owner’s knowledge, business scale, and business life; (2) situational factor which is used as moderating variable in this study only one situational factor that is using of accounting information.